Osteopontin-integrin interaction as a novel molecular target for antibody-mediated immunotherapy in adult T-cell leukemia. Issue 1 (December 2015) - Maeda, Naoyoshi; Ohashi, Takashi; Chagan-Yasutan, Haorile; Hattori, Toshio; Takahashi, Yayoi; Harigae, Hideo; Hasegawa, Hiroo; Yamada, Yasuaki; Fujii, Masahiro; Maenaka, Katsumi; Uede, Toshimitsu
Abstract Background Adult T-cell leukemia (ATL) is a CD4+ T-cell neoplasm with a poor prognosis. A previous study has shown that there is a strong correlation between the secreted matricellular protein osteopontin (OPN) level and disease severity in ATL patients. Here, we investigated the role of OPN in ATL pathogenesis and the possible application of anti-OPN monoclonal antibody (mAb) for ATL immunotherapy in NOD/Shi-scid, IL -2Rg null (NOG) mice. Results Subcutaneous inoculation of ATL cell lines into NOG mice increased the plasma level of OPN, which significantly correlated with metastasis of the inoculated cells and survival time. Administration of an SVVYGLR motif-recognizing anti-OPN mAb resulted in inhibition not only of tumor growth but also of tumor invasion and metastasis. The number of fibroblast activating protein-positive fibroblasts was also reduced by this mAb. We then co-inoculated mouse embryonic fibroblasts (MEFs) isolated from wild-type (WT) or OPN knockout mice together with ATL-derived TL-OmI cells into the NOG mice. The mice co-inoculated with WT MEFs displayed a significant decrease in survival relative to those injected with TL-OmI cells alone and the absence of OPN in MEFs markedly improved the survival rate of TL-OmI-inoculated mice. In addition, tumor volume and metastasis were also reduced in the absence of OPN. Conclusion We showed that the xenograft NOG mice model can be a useful system for assessment of the physiological role of OPN in ATL pathogenesis. Using this xenograft model, we found that fibroblast-derived OPN was involved in tumor growth and metastasis, and that this tumor growth and metastasis was significantly suppressed by administration of the anti-OPN mAbs. Our findings will lead to a novel mAb-mediated immunotherapeutic strategy targeting against the interaction of OPN with integrins on the tumor of ATL patients.